الأبعاد الاقتصادية لنمط الحياة الإسلامي - دراسة في تعزيز مكانة الاقتصاد الإسلامي ودوره في اقتصاديات الدول الإسلامية - - سعيداني, سميرة; زنكري, ميلود (جامعة الوادي - University of Eloued, 2020)
الاهتمام بنمط الحياة الإسلامي كأحد روافد الاستثمار والتنمية يعتبر من بين القضايا المستجدة في مجال الاقتصاد الإسلامي، وفي هذا الإطار تأتي دراستنا لبحث كيفية تفعيل الأبعاد الاقتصادية لنمط الحياة الإسلامي في مختلف المجالات، وبما يحقق تعزيز مكانة الاقتصاد الإسلامي ودوره في دعم وتحقيق التنمية المستدامة لاقتصاديات الدول الإسلامية، وذلك في إطار خصائص الاقتصاد الإسلامي ومقاصد الشريعة، وفي ظل التجارب الرائدة لبعض الدول الإسلامية، التي كان فيها للاستثمار في نمط الحياة الإسلامي إسهاماً واضحاً في دعم النشاط الاقتصادي وزيادة الدخل وتحقيق السعادة والرفاهية لأفراد المجتمع. الكلمات المفتاح : نمط الحياة الإسلامي ؛ أبعاد اقتصادية ؛ اقتصاد إسلامي Abstract: Attention to the Islamic way of life as one of the sources of investment and development is one of the emerging issues in the field of Islamic economics, and in this context comes our study to examine how to activate the economic dimensions of the Islamic lifestyle in various fields, in order to reinforce the status of the Islamic economy and its role in supporting the sustainable development of Islamic countries economies, in the context of the characteristics of the Islamic economy and the purposes of Sharia, and in light of the pioneering experiences of some Islamic countries, where investment in the Islamic lifestyle has made a clear contribution to support economic activity and increase income and achieve the Usually well-being of the members of the community. Keywords: Islamic lifestyle ; economic dimensions ; Islamic economy
Economic Dimensions of the Islamic Lifestyle A study on reinforcement the Islamic economy and its role in the economies of Islamic countries
Keywords: نمط الحياة الإسلامي ؛ أبعاد اقتصادية ؛ اقتصاد إسلامي